A fairness-based MAC protocol for 5G Cognitive Radio Ad Hoc Networks. (1st June 2018) - Li, Aohan; Han, Guangjie
Abstract: Fifth Generation (5G) technique aims at achieving high data rate and capacity for large numbers of users. Cognitive Radio (CR) is a promising technical to boost the development of 5G networks, which can significantly increase the spectrum efficiency by letting unlicensed Secondary Users (SUs) utilize the idle licensed spectrum without interfering licensed Primary Users (PUs) dynamically. Owing to dynamic available channels, SUs need firstly meet with their target SUs on common available channels to realize communications rapidly in CR Ad Hoc Networks (CRAHNs). Channel Hopping (CH) is a superior technique for achieving rendezvous in CRAHNs. Most of existing researches on CH problem focus on designing CH sequences that can make SUs rendezvous with each other quickly. For reducing congestion, the CH protocols spread the rendezvous in time and channel in general. However, the handshaking process for data link establishment is barely considered. Besides, there is few research on handshaking process in CRAHNs considering fair data link allocation among SUs. In this paper, we first propose novel structures for Request To Send (RTS) frame and Clear To Send (CTS) frame, which combined the characteristics of CRAHN. Then, we present a Fairness-based MAC (FMAC) protocol, which considers fair data link allocation among SUs. Simulation results demonstrate that our proposed protocol gains better performance in terms of time and fairness.